Asupan Mikronutrien, Kadar Hemoglobin dan Kesegaran Jasmani Remaja Putri - Citta Cendani; Etisa Adi Murbawani (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTMicronutrient intake, hemoglobin levels and physical fitness amongst female adolescentsBackground: Female adolescents is a group that is suspectible to anemia. Iron, zinc, copper, folic acid, vitamin B6 and vitamin B12 intake are factors among others that influence hemoglobin level. People with anemia would have the low physical fitness. The objective of this study was to understand the association between micronutrient intake (iron, zinc, copper, folic acid, vitamin B6, vitamin B12) with hemoglobin level, and hemoglobin level with physical fitness of female adolescents.Method: The design of this study was a cross sectional and the number of subject were 40 chosen by simple random sampling from 10th and 11th grade students that fulfill the inclusion criteria. Data on nutrients intake were obtained using semi quantitative food frequencies. The hemoglobin level was measured by cyanmethaemoglobin method, whereas physical fitness level was measured byharvard step test.Results: There were 32 subjects (80%) categorized as having very low and low from physical fitness. There were 10 subjects (25%) anemic. Eight subjects had low from physical fitness. There were significant associations between iron, zinc, copper, folic acid and vitamin B6 intake with hemoglobin level. There were no significant association between vitamin B12 with hemoglobin level.Regression analysis showed that iron intake contributed 67.7% variant to hemoglobin level. There were no significant association between hemoglobin level with physical fitness after controlled by nutritional status and physical activity.Conclusion: Intake of Fe, Zn, Cu, folic acid and B6 are associated with hemoglobin level, but hemoglobin level is not associated with physical fitness.Keyword: Female adolescents, physical fitness, hemoglobin, iron, zinc, copper, folic acid, vitamin B6, vitamin B12ABSTRAKLatar belakang: Remaja putri merupakan golongan yang rawan terhadap anemia. Faktor-faktor yang mempengaruhi terjadinya anemia diantaranya adalah asupan mikronutrien seperti besi, seng, tembaga, folat, vitamin B6, vitamin B12. Seseorang yang mengalami anemia dapat memiliki tingkat kesegaran jasmani yang kurang. Tujuan penelitian ini adalah untuk mengetahui hubungan antara asupan mikronutrien (besi, seng, tembaga, folat, vitamin B6, vitamin B12) dengan kadar hemoglobin dan hubungan kadar hemoglobin dengan kesegaran jasmani remaja putri.Metode: Desain penelitian cross sectional dengan jumlah subyek 40 dipilih secara simple random sampling dari kelas X dan XI yang memenuhi kriteria inklusi. Data asupan diperoleh dengan semi quantitative food frequencies. Kadar Hb diukur dengan metodecyanmethaemoglobin, sedangkan tingkat kesegaran jasmani diukur dengan metode harvard step test.Hasil: Sebanyak 32 subyek (80%) termasuk dalam kategori tingkat kesegaran jasmani sangat kurang sampai kurang. Sebanyak 10 subyek (25%) termasuk dalam kategori anemia. Sebanyak 8 subyek diantaranya memiliki tingkat kesegaran jasmani kurang. Ada hubungan antara asupan besi, seng, tembaga, folat, vitamin B6 dengan kadar hemoglobin. Analisis data dengan uji regresi didapatkan bahwa 67,7% kadar hemoglobin dapat dijelaskan oleh asupan zat besi. Tidak ada hubungan antara asupan vitamin B12 dengan kadar hemoglobin. Tidak ada hubungan antara kadar hemoglobin dengan kesegaran jasmani setelah dikontrol dengan status gizi dan aktivitas fisik .Simpulan: Asupan Fe, Zn, Cu, asam folat dan B6 berhubungan dengan kadar hemoglobin, namun kadar hemoglobin tidak berhubungan dengan kesegaran jasmani